BRAND LOYALTY: A LITERATURE REVIEW - Niken Permata Sari; Bhenu Artha; Antonius Satria Hadi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Brand loyalty has been of interest to researchers for many decades and known as an amicable attitude, also commitment toward a particular brand, builds around consumer satisfaction and leads to continued maintenance and purchasing of that brand. Brand loyalty consists of attitudinal and behavioral loyalty, and all of which contribute to brand performance. The concept of brand loyalty has been shown to have two components: an attitudinal component and a behavioral component. Brand loyalty is a driving force for business growth and an important asset for businesses, as it ensures stable and sustainable profits for the company and is an important factor for consumers. Dissatisfied customers can have a significant impact on business operations through negative reviews, therefore managing loyal customers is an important way to strengthen customer relationships. The objective of this research is to determine the factors associated with brand loyalty. We presented a literature study using systematic literature review of relevant publications and as a result of this process, 22 articles are included and then examined the bibliographical references to check the validity of the inquiry and to avoid any potential omissions. We identify several variables that associate with brand loyalty. Practical implications are also presented here.